2021
DOI: 10.1097/aud.0000000000001049
|View full text |Cite
|
Sign up to set email alerts
|

Can Cochlear Implantation in Older Adults Reverse Cognitive Decline Due to Hearing Loss?

Abstract: Introduction: Older adults with late-onset hearing loss are at risk for cognitive decline. Our study addresses the question of whether cochlear implantation (CI) can counteract this potential influence. We investigated whether cognitive performance in older adults with severe and profound hearing loss improves 12 months after CI to a level comparable to controls with normal hearing, matched for age, sex, and education level.Design: This cohort study was performed at two tertiary referral centers. The study inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 107 publications
1
23
0
3
Order By: Relevance
“…Zhan et al found only a correlation of sentence recognition in quiet after 6 months with the incompatible Stroop and the Symbol Span test, but not for the Digits or Object Span test ( Zhan et al, 2020 ). Huber et al reported a correlation of an improvement in the Clock Drawing test with monosyllabic and sentence recognition in quiet 3 months post-implantation, but not after 12 months ( Huber et al, 2021 ). Mosnier et al found no association between speech perception in quiet or in noise and in cognitive measures ( Mosnier et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhan et al found only a correlation of sentence recognition in quiet after 6 months with the incompatible Stroop and the Symbol Span test, but not for the Digits or Object Span test ( Zhan et al, 2020 ). Huber et al reported a correlation of an improvement in the Clock Drawing test with monosyllabic and sentence recognition in quiet 3 months post-implantation, but not after 12 months ( Huber et al, 2021 ). Mosnier et al found no association between speech perception in quiet or in noise and in cognitive measures ( Mosnier et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…But even in this high-quality study, the sample size was small and inhomogeneous and bias cannot be ruled out ( Mertens et al, 2021 ). Another approach was applied by Huber et al (2021) . Twenty-nine adult subjects aged 60–80 years scheduled for cochlear implantation and an age- and education-matched control group of normal-hearing subjects were enrolled in this study.…”
Section: Discussionmentioning
confidence: 99%
“…CI use could also contribute to working against the psychological and social deficits of these elderly people. Huber et al (2021) also describe that the group with hearing loss shows significantly more depressive problems but not more anxiety than their normal hearing peers in the control group. Population studies ( Gopinath et al, 2009 ; Li et al, 2014 ; Hsu et al, 2016 ) show that hearing loss in adulthood increases the likelihood of developing depressive problems and disorders.…”
Section: Cognitive Decline In the Elderlymentioning
confidence: 81%
“… Huber et al (2021) have studied the central question of whether cognitive changes following CI fitting are large enough to completely reverse cognitive decline due to hearing impairment, back to the levels comparable to normal-hearing participants. To do this, they compared data from participants in an age-matched normal-hearing control group of over 12 months in addition to the patient group with hearing loss.…”
Section: Cognitive Decline In the Elderlymentioning
confidence: 99%
See 1 more Smart Citation